Arab Open and Virtual Universities - Porcaro, David (International Higher Education, 2009)
The landscape of online and virtual universities has been expanding in the Arab world in the past decade. Enrollments are rising steadily, allowing access to higher education for students at home and overseas. As growth continues, more centralization, institution-created content, and quality assurance may be required.